Main properties of steviol glycosides and their potential in the food industry: a review. (7th March 2014) - González, Cesar; Tapia, María; Pérez, Elevina; Pallet, Dominique; Dornier, Manuel
<x content-type="archive" xml:space="preserve">Abstract</x> Introduction. In recent decades, there has been increased interest in developing natural non-caloric sweeteners, providing sensory properties similar to sucrose. One of the most promising alternatives is the steviol glycosides, high-sweetness compounds extracted from the leaves of Stevia rebaudiana Bertoni. Characteristics and properties. In this review article, the characteristics of this plant are described. According to the relevant literature data, this review provides insight into the major steviol glycosides as well as their main characteristics and properties. Toxicity and legislation. We describe the current situation on the toxicity and the legal framework of the above sweeteners. Extraction techniques. This review describes the techniques developed for extraction and purification, including conventional extraction with water/solvent, ion exchange, enzymatic extraction, supercritical fluid and with a focus on membrane filtration, for its proven advantages in the purification of aqueous extract obtained by leaching of the leaves. Applications. This review also presents various evidence relating to the implementation of steviol glycosides in the food industry, with an emphasis on their use in the formulation of fruit juices. Conclusions. Finally, the future prospects of these natural sweeteners are presented. They highlight the need for research in this area, and the great appeal and commercial potential of such compounds, which should be focused on continuous assessment in relation to issues such as the intensity, persistence of sweetness and the absence of other residual flavors, in order to ensure their acceptance, preference and choice by the general public.